Pregnancy Outcomes after Preeclampsia: The Effects of Interpregnancy Weight Change - Tabet, Maya; Banna, Soumya; Luong, Lan; Kirby, Russell; Chang, Jen Jen (American Journal of Perinatology, 2020)
Objective This study aimed to examine the effects of interpregnancy weight change on pregnancy outcomes, including recurrent preeclampsia, preterm birth, small-for-gestational age (SGA), large-for-gestational age (LGA), and cesarean delivery, among women with a history of preeclampsia. We also evaluated whether these associations were modified by prepregnancy body mass index (BMI) category in the first pregnancy (BMI < 25 vs. ≥25 kg/m2) and if associations were present among women who maintained a healthy BMI category in both pregnancies.Study Design We conducted a population-based retrospective cohort study including 15,108 women who delivered their first two nonanomalous singleton live births in Missouri (1989–2005) and experienced preeclampsia in the first pregnancy. We performed Poisson regression with robust error variance to estimate relative risks and 95% confidence intervals for outcomes of interest after controlling for potential confounders.Results Interpregnancy weight gain was associated with increased risk of recurrent preeclampsia, LGA, and cesarean delivery. These risks increased in a “dose–response” manner with increasing magnitude of interpregnancy weight gain and were generally more pronounced among women who were underweight or normal weight in the first pregnancy. Interpregnancy weight loss exceeding 1 BMI unit was associated with increased risk of SGA among underweight and normal weight women, while interpregnancy weight loss exceeding 2 BMI units was associated with reduced risk of recurrent preeclampsia among overweight and obese women.Conclusion Even small changes in interpregnancy weight may significantly affect pregnancy outcomes among formerly preeclamptic women. Appropriate weight management between pregnancies has the potential to attenuate such risks.Key Points
Keywords: interpregnancy; preeclampsia; pregnancy outcomes; weight change